PERLINDUNGAN KONSUMEN ATAS WANPRESTASI DEVELOPER TERHADAP BANGUNAN KPR BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Arifin, Jajang (Universitas Wiralodra, 2019)
The binding agreement on the sale and purchase of land and buildings is a preliminary agreement prior to the signing of the legitimate deed of sale and purchase, containing the provisions of sale and purchasing regulations, which stipulates the legal provisions of the sale and purchases party. The parties bound in the agreement should mutually carry out their obligations and accept their rights. The developer is obliged to build and give the land and its buildings to the consumer. This study used a doctrinal legal research model with the method of statutory approach. The research specification is analytical descriptive which refers to the use of secondary data. In this study, the researcher examined the legislation and other literature data which were subsequently analyzed qualitatively. This study intended to determine the legal protection for consumers of developers who do default, and to find out sanctions for developers who do default on consumers based on the constitution No. 8 of 1999 concerning consumer protection. After conducting a complete study or analysis of this case, it can be concluded that the buyer as a consumer is entitled to get legal protection for defaults from the developer. It is because between the two, there is a bond in a binding agreement of sale and purchase. The developer has violated article 8 section (1) letter f, article 7 letter a, article 4 (letters a, b, c and h), article 16, article 19, and article 62 section (1) and (2) of the constitution regarding the consumer protection law (UUPK). Other criminal threats for developers who build housing without the comply from the agreed criteria, specifications, and requirements, are set out in article 134 in conjunction with article 151 number 1 of 2011 of the constitution concerning housing and settlement areas, namely a maximum fine of 5 billion rupiah.